PENYALAHGUNAAN ALOKASI DANA DESA OLEH KEPALA DESA - Mutmainnah Maharani; Andi Agustang; Idham Irwansyah Idrus (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2023)
Corruption has always been the most frequent news in Indonesia, every year there are officials who are dragged into corruption cases. All forms and methods have been carried out by the State to eradicate the movement of corruption. However, until now corruption still occurs in Indonesia which in the end is very detrimental to the people and the State. The purpose of this research is to find out: (1) the factors of corruption. (2) Law enforcement against misuse of village funds according to the provisions of the Corruption Crime Act. This study uses descriptive methods, data collection techniques through library research and qualitative data analysis to reach conclusions. Based on the results of the research, it shows that the factor in the occurrence of criminal acts of corruption is solely because of the material and feeling dissatisfied with what he gets, which makes him greedy and abuses his position as village head. It all comes from the personality of the village head himself as well as from environmental factors. In law enforcement according to the provisions of the Corruption Crime Act that occurred in Polewali Mandar, namely law enforcement which is carried out by taking action against a crime or violation by following existing SOPs and imposing sanctions or punishment on perpetrators of corruption in accordance with existing provisions under the Act.